Pengaruh Model Flipped Classroom Terhadap Kompetensi Strategis Matematis Siswa Ditinjau dari Kemandirian Belajar - Sari, Hamelia Puspita; Rikayanti; Sutirna (Papanda, 2025)
This study aims to determine the effect of the flipped classroom learning model on students' mathematical strategic competencies in terms of their level of learning independence. Strategic competencies are an important aspect of mathematical proficiency, which includes the ability to formulate problems, represent them, and solve mathematical problems. This study employs an experimental method with a factorial design. The research sample consists of seventh-grade students at a junior high school in Karawang during the 2024/2025 academic year, divided into a control group and an experimental group, selected using purposive sampling. The research instruments consisted of a learning independence questionnaire and pre- and post-tests of mathematical strategic competence. Data analysis was conducted using normality tests, homogeneity tests, t-tests, effect size tests, one-way Anova, and two-way Anova. The results of the study indicate that: (1) there is an effect of the flipped classroom model on students' mathematical strategic competencies, (2) there are differences in mathematical strategic competencies based on the level of learning independence in the application of the flipped classroom model, (3) there is no interaction between the learning model and the level of learning independence on students' mathematical strategic competencies. These findings indicate that both the learning model and learning independence individually influence mathematical strategic competence. The flipped classroom model has been proven effective for students with various levels of learning independence.